ANALISIS KEBUTUHAN GURU AGAMA HINDU DI KOTA MATARAM DAN SIGNIFIKANSINYA DENGAN LULUSAN INSTITUT AGAMA HINDU NEGERI GDE PUDJA MATARAM - Ida Bagus Benny Surya Adi Pramana; I Made Ngurah Oka Mahardika; I Made Sudarma; Ida Bagus Made Arjana (Jurnal Cakrawala Ilmiah, 2022)
The shortage of Hindu Religion Teachers is one of the main problems for the world of education. We hope that with the large number of Hindu religious colleges and graduates of the Hindu Religious Education S1 study program, it is hoped that it will fill the shortage of Hindu religious teachers and the opportunity to be accepted as a Hindu religion teacher is quite large according to existing needs. The shortage of teachers causes the quality of Hindus to be low because they are taught by incompetent teachers. The city of Mataram, which is the city center in the West Nusa Tenggara area, is a barometer to determine the quality of Hindus in West Nusa Tenggara. The Hindu Institute of Religion, which is the only Hindu religious college in West Nusa Tenggara, plays a major role in producing quality Hindu religious educators. This theme is very interesting because from here we can find out what are the obstacles in Hindu religious education from elementary, middle and upper levels. The output of this research is expected to be an input for the Mataram city government and the Mataram City education office to increase the quota of Hindu religious teachers in Mataram City. The formulation of the problem, namely: 1. How to analyze the needs of Hindu religious teachers based on a SWOT analysis? And 2. What are the opportunities and challenges of IAHN Gde Pudja Mataram as a producer of Hindu religious teachers in Mataram City in anticipating these opportunities and challenges? The methodology used in this research is qualitative with the research location is Mataram City.Conclusion: 1. From the results of the analysis of the shortage of Hindu Religion Teachers from elementary to high school levels are 25 people. 2. From the results of the SWOT analysis, we have the strength that we have 9 council members at the Mataram city level and 1 at the NTB provincial level and the Gde Pudja Mataram State Hindu Institute Campus which produces many prospective Hindu religious teachers. The weaknesses are weak lobbying and coordination of each institution and the government's lack of attention to recruiting Hindu religious teachers. The opportunities are: there is still a lack of Hindu religious teachers and the majority of Hindus are in the city of Mataram. Meanwhile, the challenges are that schools are no longer allowed to recruit honorary teachers, the salaries of honorary teachers are small, there has been no recruitment of Hindu religious teachers for 4 years and there is no formal boarding school. 3. 90% of Hindu Religion Teachers in Mataram City are graduates of IAHN Gde Pudja Mataram 4. Opportunities for Alumni S1 Hindu Religious Education IAHN Gde Pudja Mataram are: as prospective Hindu religious teachers, prospective researchers and educational staff and the challenge is that alumni of S1 Hindu Religious Education must improve their level of education.